The Study of Green Building Application Awareness - Yusoff, M. N; Nawi, M.N.M; Ibrahim, S.H. (UTM Press, 2015)
The Green Building, or known as Environmentally Friendly Building is not only closely examined in terms of its design, but also the capacity of the building and its surrounding in reducing the impact to the environment, saving energy, water, safeguarding the internal air quality, and further mitigating the number of health problems to the inhabitants. The study involves 80 respondents, whereby 20 respondents are developers/contractors; 20 respondents are consultants; 20 respondents from the Local Authority and 20 respondents are academicians in the northern part of the Peninsula. Through the technique of principal axis factoring, 10 items had successfully been placed in the screening analysis. Two components that had been formed are namely i) main issue and ii) government’s effort. It is anticipated that the key players (the developers, consultants, contractors, and academicians) understood and realised the importance of the environment and what is going around them in the world today.